2017
DOI: 10.1369/0022155417729154
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Distribution of Collagen II and Perifibrillar Adapter Proteins in Healthy and Osteoarthritic Human Knee Joint Cartilage

Abstract: Perifibrillar adapter proteins, interconnecting collagen fibrils, and linking the collagen network with the aggrecan matrix seem to play a crucial role in the pathogenesis of osteoarthritis (OA). Therefore, we examined immunohistochemically the extracellular distribution of collagen II and the main perifibrillar adapter proteins-collagen IX, decorin, cartilage oligomeric matrix protein (COMP), and matrilin-3-in human samples of healthy (n=4) and OA (n=42) knee joint cartilage. Histopathology assessment was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…Similar conclusions were drawn by Verma and Dalal, who found that sCOMP was associated with pain but not radiological changes [16]. Furthermore, they described an overall negative association between the level of sCOMP and disease progression-an association which might be explained by the gradual depletion of interterritorial COMP found in human late-stage OA cartilage [19]. Nevertheless, Verma and Dalal proposed that sCOMP might serve as a prognostic marker, which allows determining patients at risk of rapid disease progression in the early stages of OA [16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar conclusions were drawn by Verma and Dalal, who found that sCOMP was associated with pain but not radiological changes [16]. Furthermore, they described an overall negative association between the level of sCOMP and disease progression-an association which might be explained by the gradual depletion of interterritorial COMP found in human late-stage OA cartilage [19]. Nevertheless, Verma and Dalal proposed that sCOMP might serve as a prognostic marker, which allows determining patients at risk of rapid disease progression in the early stages of OA [16].…”
Section: Discussionsupporting
confidence: 78%
“…In the late stages of OA, the elevated synovial fluid and serum levels of COMP (sCOMP) are declining probably due to its depletion in highly degenerated tissue [16,18,19]. However, locally high expression was reported in chondrocytes adjacent to severely damaged cartilage, indicating a possible implication in insufficient repair processes [20].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, chondrodysplasia-causing mutations in COMP, collagen IX, or MATN3 are frequently associated with premature osteoarthritis. Matrilin-3 is present at low levels in the joint articular surface and its deposition is upregulated in cartilage and in the synovial fluid of patients with OA as a consequence of cartilage degradation [56][57][58][59][60]. Studies with recombinant MATN3 and human primary chondrocytes have revealed that MATN3 exhibits a context-dependent anabolic or catabolic function by influencing the expression of pro-inflammatory cytokines, ECM degradation enzymes, and ECM synthesis [59,[61][62][63] through the modulation of protein kinase B (AKT) [59], interleukin-6 [62], and interleukin-1 [63,64] signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COMP interacts with growth factors, and besides regulating extracellular matrix composition and assembly, it also affects cellular functions such as proliferation, differentiation, and attachment of cells . Several studies have shown that the localization and expression of COMP differs between healthy hyaline articular cartilage and osteoarthritic cartilage . In addition, elevated serum COMP levels have been reported in OA, rheumatoid arthritis, and injured knees .…”
mentioning
confidence: 99%
“…32 Several studies have shown that the localization and expression of COMP differs between healthy hyaline articular cartilage and osteoarthritic cartilage. 33 In addition, elevated serum COMP levels have been reported in OA, 34,35 rheumatoid arthritis, 36 and injured knees. 37 COMP has also been detected in human adipose tissue and there are differences in expression between abdominal fat and gluteal fat.…”
mentioning
confidence: 99%